Former des « personnalités », valoriser la créativité. La permanence de la forme scolaire dans l'enseignement supérieur de design de mode - Nicolas Divert
Claiming the professionalization of their graduates, courses in Design state that they seek to promote the singularity of their students and participate in building 'personalities'. The underlying individualisation questions the transmission of knowledge within the prescribed framework of BTS (technical diploma). This article seeks to question, via qualitative research, the peculiarities of education in applied arts specializing in fashion creation in the framework of a BTS in Fashion Design, Textile and Environment (fashion pathway). If, a priori, the stated aims and objectives and the valorisation of the aforementioned approach seem to be far from the official curriculum, the latter is still imposed on teaching practices and requirements.